Alveolar microbiota profile in patients with human pulmonary tuberculosis and interstitial pneumonia. (February 2020) - Vázquez-Pérez, Joel Armando; Carrillo, Concepción Ortega; Iñiguez-García, Marco Antonio; Romero-Espinoza, Ivan; Márquez-García, José Eduardo; Falcón, Luisa I.; Torres, Martha; Herrera, María Teresa
Abstract: Background: The presence of the human lung microbiota has been demonstrated in patients with different lung diseases, mainly in sputum samples. However, for study of the alveolar microbiota, a bronchoalveolar lavage (BAL) sample represents the lower respiratory tract (LRT) environment. It is currently unknown whether there is a specific alveolar microbiota profile in human lung diseases, such as pulmonary tuberculosis (TB) and interstitial pneumonia (IP). Methods: BAL samples from six active TB patients, six IP patients and ten healthy volunteers were used for DNA extraction followed by amplification of the complete bacterial 16S ribosomal RNA gene (16S rDNA). The 16S rDNA was sequenced with a MiSeq Desktop Sequencer, and the data were analysed by QIIME software for taxonomic assignment. Results: The alveolar microbiota in TB and IP patients and healthy volunteers was characterized by six dominant phyla, Firmicutes, Proteobacteria, Bacteroidetes, Actinobacteria, Fusobacteria and Cyanobacteria. A significant reduction in the abundance of Firmicutes was observed in IP patients. In TB and IP patients, the diversity of the alveolar microbiota was diminished, characterized by a significant reduction in the abundance of the Streptococcus genus and associated with increased Mycobacterium abundance in TB patients and diminished Acinetobacter abundance in IP patients with respect to their abundances in healthy volunteers. However, an important difference was observed between TB and IP patients: the Fusobacterium abundance was significantly reduced in TB patients. Exclusive genera that were less abundant in patients than in healthy volunteers were characterized for each study group. Conclusions: This study shows that the alveolar microbiota profile in BAL samples from TB and IP patients, representing infectious and non-infectious lung diseases, respectively, is characterized by decreased diversity.